Effectiveness and Efficiency of Financial Management in Village-Owned Enterprises (BUMDes) : A Case Study of Sindang Jaya Village, Sindang Kelingi District - Novriza Wahyu Ardiansyah; Zenniza Ela Manata; Sucipto Febrianto (Brilliant International Journal Of Management And Tourism, 2026)
This study aims to analyze the level of effectiveness and efficiency in the financial management of the Village-Owned Enterprise (BUMDES) Lestari Jaya, located in Sindang Jaya Village, Sindang Kelingi District. Village-Owned Enterprises serve as an instrument for enhancing local economic independence and improving community welfare through business innovation and participatory management. The research applies a qualitative descriptive method, involving observation, interviews, and documentation of BUMDES financial reports from 2021 to 2023. Findings show that BUMDES Lestari Jaya managed its finances effectively and efficiently, achieving effectiveness levels of 96%, 95%, and 98.46% for 2021–2023 respectively, and efficiency ratios of 50%, 50%, and 49.23%. These results indicate that the enterprise has implemented sound financial management principles, including accountability, transparency, and cost control. The study concludes that effective financial governance in BUMDES contributes significantly to sustainable village development and community empowerment.